نئے پیش آمدہ مسائل ِطہارت کے حل میں قواعد فقہیہ سے استفادہ کی جہات: Aspects of Using Legal Maxims in Solving Modern Problems of purification - Dr. Hafiz Irfanullah; Dr. Tahir Masood Qazi (AL-IDRAK JOURNAL, 2024)
Allah Ta'ala has entrusted the ability to change human nature. It is such a beautiful quality to which man determines the steps of development from where he has reached. From the human lifestyle to his food, his necessities to compliments and luxuries, the meaning of everything has changed so much that what has become our necessity some time ago was considered as compliments and luxuries. This is the reason that the Islamic Sharia has described such teachings in the light of which solutions to problems can be found according to the changes in times and circumstances. This is one of the beauty of the Islamic Sharia which distinguishes it from other religions. It is a necessary thing that the change of circumstances and times affects Sharia issues. This is the reason why the jurists of all eras made this debate a subject of research. They provided arguments on this in their books, reviewed the influencing situations and times, explained its rules and regulations, and explained the problems keeping in mind the aspect of the Shariah for the Muslim Ummah and where A group of jurists gave special importance to the rules of jurisprudence called legal maxims, made a successful attempt to understand and interpret them, as a result of which the solution of jurisprudential problems became easier. There are also important rules related to the situation and time, in light of which newly occurring problems can be solved. In this article, the contemporary problems related to purity and the aspects of using maxims related to the exceptions of circumstances and times to solve these problems have been highlighted.